CML CELEBRATES MALAYSIAN HEROES AT “SPEAK UP!” 2024 - Wan Noor Farah, Wan Shamsuddin; Nor Yazi, Khamis; Azwin Arif, Abdul Rahim; Nur syafawati, Sabuan; Suriayati, Mohd Sidek (Centre for Modern Languages, 2024)
Gambang, 20 September 2024 - A two-day event “Speak Up!”, was successfully held on 18 and 19 September 2024, aimed at improving the communication skills of personnel from the 4th Brigade Headquarters (Mechanize), Kuantan Air Base, and Naval Region 1 Headquarters. This comprehensive program focused on enhancing both verbal and non-verbal communication, as well as fostering confidence among participants.